1965
DOI: 10.1085/jgp.48.5.957
|View full text |Cite
|
Sign up to set email alerts
|

Cat Heart Muscle in Vitro

Abstract: The cells of cat right ventricular papillary muscles were depleted of K and caused to accumulate Na and water by preincubation at 2-3°C. The time courses of changes in cellular ion content and volume and of the resting membrane potential (V,,) were then followed after abrupt rewarming to 27-28C. At physiological external K concentration ([K] = 5.32 mM) recovery of cellular ion and water contents was complete within 30 minutes, the maximal observable rates of K uptake and Na extrusion (Ammol cell ion/ (kg dry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

1972
1972
1994
1994

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(37 citation statements)
references
References 13 publications
0
36
1
Order By: Relevance
“…In cardiac muscles, the active Na extrusion seemed to occur after a period of "Na loading" produced by several maneuvers (e.g., K-free perfusion, application of cardiac glycosides, lowering the temperature, and high frequency of stimulation) (PAGE and STORM, 1965;TAMAI and KAGIYAMA, 1968;GLITSCH, 1969GLITSCH, , 1972VASSALLE, 1970;CARPENTIER and VASSALLE, 1971;HIRAOKA and HECHT, 1973;AKASU et al, 1978;GADSBY and CRANEFIELD, 1979a, b;GLiTSCH and PUSCH,1980;NOSEK,1980). We assessed the Na, K-pump activities in both Epi and Endo from the hyperpolarization which followed high frequency drive ("post-overdrive hyperpo- during and after 1-min stimulation (3.3-3.8 Hz).. E1, E2, E3, and E4 show, respectively, the pre-stimulation diastolic membrane potential, the maximum depolarized potential during the stimulation, the potential at the end of the stimulation, and the maximum hyperpolarized potential after cessation of the stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cardiac muscles, the active Na extrusion seemed to occur after a period of "Na loading" produced by several maneuvers (e.g., K-free perfusion, application of cardiac glycosides, lowering the temperature, and high frequency of stimulation) (PAGE and STORM, 1965;TAMAI and KAGIYAMA, 1968;GLITSCH, 1969GLITSCH, , 1972VASSALLE, 1970;CARPENTIER and VASSALLE, 1971;HIRAOKA and HECHT, 1973;AKASU et al, 1978;GADSBY and CRANEFIELD, 1979a, b;GLiTSCH and PUSCH,1980;NOSEK,1980). We assessed the Na, K-pump activities in both Epi and Endo from the hyperpolarization which followed high frequency drive ("post-overdrive hyperpo- during and after 1-min stimulation (3.3-3.8 Hz).. E1, E2, E3, and E4 show, respectively, the pre-stimulation diastolic membrane potential, the maximum depolarized potential during the stimulation, the potential at the end of the stimulation, and the maximum hyperpolarized potential after cessation of the stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…There is a number of evidences showing that the active Na+ and K+ transport in cardiac muscles is electrogenic in that the extrusion of Na+ is not balanced by an equal uptake of K+ (PAGE and STORM, 1965;TAMAI and KAGIYAMA, 1968;VASSALLE, 1970;GLITSCH, 1972;HIRAOKA and HECHT, 1973). VASSALLE (1970) first described a post-overdrive hyperpolarization in sheep and dog Purkinje fibers and concluded that the activation of an electrogenic Na, K-pump was the major mechanism responsible for the post-overdrive hyperpolarization.…”
Section: Discussionmentioning
confidence: 99%
“…This hyperpolarization occurs only if the intracellular Na concentration has been increased during cooling (Glitsch, 1972a). It is not due to the distribution of chloride ions at the sarcolemma (Page & Storm, 1965). The amplitude of hyperpolarization is correlated with the magnitude of active Na efflux from the rewarmed cardiac cells (Glitsch, 1972a).…”
Section: Introductionmentioning
confidence: 99%
“…The cell membrane of cardiac fibres hyperpolarizes transiently during rewarming after prolonged hypothermia (Page & Storm, 1965; Glitsch, 1969;Hiraoka & Hecht, H. G. GLITSCH AND OTHERS 1973). This hyperpolarization occurs only if the intracellular Na concentration has been increased during cooling (Glitsch, 1972a).…”
Section: Introductionmentioning
confidence: 99%
“…Cooling can increase internal Na activity, [Na]i, by decreasing Na pump activity. On rewarming the tissue following such hypothermia, the resting potential transiently overshoots the control level to more negative potentials (Page & Storm, 1965;Tamai & Kagiyama, 1968;Hiraoka & Hecht, 1973;Glitsch, Grabowski & Thielen, 1978). Alternatively [Na]i can be raised by blocking the Na pump by exposing the tissue to K-depleted solutions (Noma & Irisawa, 1975;Ellis, 1977).…”
Section: Introductionmentioning
confidence: 99%